2009
DOI: 10.1174/021037009788001806
|View full text |Cite
|
Sign up to set email alerts
|

Early literacy interventions: Which activities to include? At what age to start? And who will implement them?

Abstract: ResumenThe article utilised data from two intervention studies carried out in low SES preschools in order to address issues in the realm of literacy interventions: Which components are more productive in promoting literacy skills (storybook reading or alphabetic training); at what age should these components be introduced (three or four years old); and who should implement the interventions (MA students or preschool teachers). The studies describe preplanned intensive interventions. The results demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
6
0
2
Order By: Relevance
“…It is important to remember that the data in the present study was placed in three groups according to the mother´s performance (low, intermediate or high), depending on their reader-narrator skills, however, during the first evaluation all participants showed limited abilities for the promotion of linguistic interactions in their children, and to provide them with informal teachings while reading stories. This first result confirms the information reported by previous researchers (Aram & Besser, 2009;Korat, 2011;Guevara et al, 2007) that indicate how mothers of families with a low socio cultural level may display some limited abilities to establish dialogue and to encourage linguistic and conceptual interactions to allow children´s proper development. When comparing performances and advances of the mothers and children that participated in the present study, we observed some differences between the groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is important to remember that the data in the present study was placed in three groups according to the mother´s performance (low, intermediate or high), depending on their reader-narrator skills, however, during the first evaluation all participants showed limited abilities for the promotion of linguistic interactions in their children, and to provide them with informal teachings while reading stories. This first result confirms the information reported by previous researchers (Aram & Besser, 2009;Korat, 2011;Guevara et al, 2007) that indicate how mothers of families with a low socio cultural level may display some limited abilities to establish dialogue and to encourage linguistic and conceptual interactions to allow children´s proper development. When comparing performances and advances of the mothers and children that participated in the present study, we observed some differences between the groups.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, families with lower economic, social and educational levels often show limited literacy practices (Aram & Besser, 2009;Korat, 2011), which translates into behavioural limitations on children. Research studying low socio-cultural Mexican families (Guevara, García, López, Delgado & Hermosillo, 2007;Rugerio & Guevara, 2014) have reported linguistic, pre-academic and conceptual skills deficiencies on preschool students and early first graders, these children may show deficits in word´s meaning, understanding stories, spontaneous expression, spatial-temporal relation, description and narration.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that include assessments of general vocabulary routinely involve interventions and longer timescales, (typically several weeks or more, see e.g., Aram & Besser, 2009;Reese & Cox, 1999;Valdez-Menchaca & Whitehurst, 1992). The dearth of meta-analyses addressing word learning from shared reading to date may well be explained by the high level of variability between measurement approaches.…”
Section: The Effects Of Shared Storybook Reading On Word Learning: a mentioning
confidence: 99%
“…In practice, some experimental assessments measure growth in the total number of words children comprehend (i.e., general vocabulary), while others measure recall or production of specific target words from the text. Studies that include assessments of general vocabulary routinely involve interventions and longer timescales, (typically several weeks or more, see, e.g., Aram & Besser, 2009; Reese & Cox, 1999; Valdez-Menchaca & Whitehurst, 1992). The dearth of meta-analyses addressing word learning from shared reading to date may well be explained by the high level of variability between measurement approaches.…”
mentioning
confidence: 99%
“…Also, girls often enter preschool with stronger literacy skills (Justice et al 2005; Ready et al 2005). Further, younger children may know less because they have had fewer learning experiences (Aram and Besser 2009; Justice et al 2005; Redford and Gildersleeve-Neumann 2009). At the family level, higher maternal education, two-parent household structures, and high involvement in learning may provide children with more opportunities to build literacy (Aikens and Barbarin 2008; Belsky and Fearon 2004; Hooper et al 2010; Janus and Duku 2007; National Early Literacy Panel (NELP) 2009; Snow, Burns, and Griffin 1998; Suizzo and Stapleton 2007), whereas poverty limits access to learning resources (Bradley et al 2001; Ryan, Fauth, and Brooks-Gunn 2006).…”
Section: Applications Of Growth Models: Early Learning and Developmentmentioning
confidence: 99%